Analisis Faktor Penentu Kepuasan Konsumen pada Rumah Makan Ondo Grill Batak di Medan - Jenni Sinurat; Ali Fikri Hasibuan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to examine the factors that influence consumer satisfaction at Ondo Grill Batak Restaurant in Medan City. The variables studied include service quality, product quality, and price as independent variables, while consumer satisfaction is set as the dependent variable. This research employs a descriptive quantitative approach using a survey method through the distribution of questionnaires to customers who have visited and experienced the restaurant’s services. The sampling technique used is non-probability sampling with a purposive sampling approach to ensure that respondents are relevant to the research objectives. The analysis results show that partially, service quality, product quality, and price have a positive and significant effect on consumer satisfaction. Simultaneously, these three independent variables also have a positive and significant influence on consumer satisfaction, with a contribution of 92%, while the remaining 8% is influenced by other factors outside this study, such as promotion, ambiance, and customer loyalty. These findings emphasize that improving friendly and efficient service, maintaining consistent product quality, and setting prices that match the perceived value are key strategies to enhance customer satisfaction and maintain loyalty at Ondo Grill Batak Restaurant.